Modifiable determinants of central obesity among the rural black population in the DIMAMO HDSS, Limpopo, South Africa - Ntimana, Cairo B.; Choma, Solomon S. R. (Frontiers in Public Health, 2023)
Background: Central obesity is a leading risk factor for cardio-metabolic diseases in which body fat builds up to a particular extent and may negatively impact health. The prevalence of abdominal obesity has increased over the past ten years and now surpasses that of overall obesity. There is scarcity of data on the determinants of central obesity especially among populations residing in rural Africa. The aim of the present study was thus to determine which sociodemographic factors and lifestyle factors are associated with central obesity Method: This was a cross-sectional, retrospective study. The present study used secondary data from the AWI-Gen phase 1 study. The study comprised 791 participants of which 242 were men and 549 were women aged 40 years and above. The Participants were selected using convenient sampling. Data were analysed using the Statistical Package for Social Sciences version 27. A comparison of proportions was performed using Chi-Square whilst a comparison of means was performed using an unpaired student -t-test. The association between sociodemographic and lifestyle factors with central obesity was analysed using bivariate correlation, partial correlation, and bivariate regression analysis. The statistical significance was set at p < 0.05. Results: The proportion of central obesity in the total population was 59.9%, and significantly more women were centrally obese (79.6% vs 15.3%, p=<0.001) as compared to men. Married status correlated positively and significantly with central obesity in both bivariate and partial correlation. Moreover, binary logistic regression further confirmed the positive association between married status and central obesity. Single status correlated negatively and significantly with central obesity, the correlation remained unchanged even after controlling the age and gender. Binary logistic regression showed that unemployment correlated significantly with central obesity. The proportion of smokers was also significantly higher in participants without central obesity than in those with central obesity (87.2% vs 34.0%, p=<0.001). Smoking correlated negatively and significantly with central obesity in bivariate and partial correlation. In addition, binary logistic regression further confirmed the negative association between smoking and central obesity. Conclusion: The present study shows that in this population central obesity is determined by, gender, being unemployed, and being married.